Optimization of a Monobromobimane (MBB) Derivatization and RP-HPLC-FLD Detection Method for Sulfur Species Measurement in Human Serum after Sulfur Inhalation Treatment - Barbara Roda; Nan Zhang; Laura Gambari; Brunella Grigolo; Cristina Eller-Vainicher; Luigi Gennari; Alessandro Zappi; Stefano Giordani; Valentina Marassi; Andrea Zattoni; Pierluigi Reschiglian; Francesco Grassi (Antioxidants, 2022)
(1) Background: Hydrogen sulfide (H2S) is a widely recognized gasotransmitter, with key roles in physiological and pathological processes. The accurate quantification of H2S and reactive sulfur species (RSS) may hold important implications for the diagnosis and prognosis of diseases. However, H2S species quantification in biological matrices is still a challenge. Among the sulfide detection methods, monobromobimane (MBB) derivatization coupled with reversed phase high-performance liquid chromatography (RP-HPLC) is one of the most reported. However, it is characterized by a complex preparation and time-consuming process, which may alter the actual H2S level; moreover, a quantitative validation has still not been described. (2) Methods: We developed and validated an improved analytical protocol for the MBB RP-HPLC method. MBB concentration, temperature and sample handling were optimized, and the calibration method was validated using leave-one-out cross-validation and tested in a clinical setting. (3) Results: The method shows high sensitivity and allows the quantification of H2S species, with a limit of detection of 0.5 µM. Finally, it can be successfully applied in measurements of H2S levels in the serum of patients subjected to inhalation with vapors rich in H2S. (4) Conclusions: These data demonstrate that the proposed method is precise and reliable for measuring H2S species in biological matrices and can be used to provide key insights into the etiopathogenesis of several diseases and sulfur-based treatments.